Leadership style and organizational commitment: A study in Panasonic Energy Malaysia - Arulkumar, Muniandy (2016)
In Panasonic Energy Sdn Bhd, the research investigation had been taken to identify the relationship between the organizational commitment and the leadership style. Data for this study was gathered from a sample of 169 rater's. Questionnaire was distributed to all the operators in the Module department and total 120 questionnaires were returned. According to The Full Range Leadership Development Theory, the multifactor leadership questionnaire is utilized within the organization to determine the leadership style. Employee commitment was measured using Bagraim's (2004) Organizational Commitment, adaptation of Meyer and Allen's (1997) Three-Component Model of employee commitment. Leadership was identified as the independent variable and organizational commitment as the dependent variable. Data was obtained from questionnaires which were distributed to module production direct employee. Overall findings from this study suggest that transformational and transactional leadership plays important roles in determining levels of affective commitment, continuance commitment and normative commitment. This research therefore adds a new dimension to the body of literature that will help researchers' efforts to understand the relationship between leadership style and organizational commitment. As this research takes place in Kulim Kedah context, it contributes to the bank of findings relating to the development of organizational commitment.